EU ENLARGEMENT: TURKISH ACCESSION AND IDENTITY - Muhammad Jave Zulkarnaen (DIA: Jurnal Administrasi Publik, 2020)
Turkey is one of the most important countries for the EU because it has a strategic position in Western Europe, Eastern Europe, and even the Middle East. The good relationship between Turkey and the EU is based on history such as war, diplomacy, trade, art, cuisine, to culture. For centuries, the relationship between the two marked the deep economic, cultural, artistic, and social cooperation between the Ottoman Empire and the European powers of the fifteenth to the seventeenth centuries. At the same time, conflict and competition create an identity perception among EU countries towards Turkey. This paper attempts to explain the identity of Turkey and the European Union and to determine whether the identity as cultural or political affected the Turkish application to be a member of the European Union.